HUBUNGAN PENGETAHUAN IBU TENTANG OBESITAS BALITA DENGAN KEJADIAN OBESITAS PADA BALITA DI NAGARI KOTO RAJO KAB. PASAMAN TAHUN 2015 - Fransiska, Mellia; Rahmadani, Melda (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Liver cirrhosis is often found in old age, the disease can cause death if not treated immediately. Data from the Provincial Health Office in Padang, liver cirrhosis ranks 17th in 2015 ie 213 cases. The number of cases of liver cirrhosis at IbnuSina Islamic Hospital BukittinggiYarsi West Sumatera in 2016 (January-December) has reached 30 cases. The purpose of the study was to determine the risk factors of liver cirrhosis incidence at Ibnu Sina Hospital BukittinggiYarsi West Sumatra. The research design used was analytical research using